TEACHERS’ STRATEGIES IN IMPROVING EARLY CHILDHOOD QUR’AN READING SKILLS THROUGH THE IQRO METHOD - Riris Wahyuningsih; Habibah Afiyanti Putri; Bella Arini Haq; Ria Octa viana (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
This study aims to analyze teacher strategies in implementing the Iqro method for Quran learning in early childhood in the digital era. Using a qualitative approach with a basic research design, the study was conducted at Aisyiyah Bustanul Athfal 2 Kindergarten in Muncar, Banyuwangi during the period of February-May 2025. Data were collected through participatory observation, in-depth interviews with 6 informants (the principal, 4 class teachers, and the program coordinator), and documentation studies. Data analysis using the Miles-Huberman interactive model includes data condensation, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Iqro method is carried out through a routine morning Quran program with the following stages: reading together, individual sorogan, independent coaching, progress evaluation, and volume increase tests. Supporting factors include the availability of guidance, individual approaches, and teacher persuasive communication. The main obstacles are the lack of interest of some students, monotonous learning, and limited teacher creativity. The Iqro method has been proven effective in improving children's Quran reading skills with indicators of increased recognition of hijaiyah letters, pronunciation of makhraj, and understanding of basic tajwid. The research recommends the development of a holistic strategy that integrates the technical aspects of reading with an understanding of spiritual meaning according to the characteristics of early childhood.